2009
DOI: 10.5694/j.1326-5377.2009.tb02876.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to addressing overweight and obesity before conception

Abstract: Objective: To investigate the issues that confront women when addressing overweight and obesity before conception. Design: Questionnaire‐based study of 412 unselected women in early pregnancy. Setting and participants: 255 women who attended a public, antenatal “first visit” clinic at a major urban obstetric hospital in Brisbane and 157 women who presented to a private obstetrician in Brisbane for a routine ultrasound scan during a 6‐week period in 2006 were surveyed. Main outcome measures: Preconception healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 24 publications
3
43
2
Order By: Relevance
“…These women were either attending a public antenatal "first visit" clinic (n = 255), or undergoing a routine private ultrasound evaluation prior to 20 weeks gestation (n = 157)[44]. 61.9% of study participants were cared for in the public sector, similar to previously published proportions from Queensland [45].…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…These women were either attending a public antenatal "first visit" clinic (n = 255), or undergoing a routine private ultrasound evaluation prior to 20 weeks gestation (n = 157)[44]. 61.9% of study participants were cared for in the public sector, similar to previously published proportions from Queensland [45].…”
Section: Methodsmentioning
confidence: 67%
“…We developed a questionnaire and surveyed 412 consecutive unselected women in early pregnancy as previously reported [43]. These women were either attending a public antenatal "first visit" clinic (n = 255), or undergoing a routine private ultrasound evaluation prior to 20 weeks gestation (n = 157)[44].…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge about risks has been shown to be lower among women with shorter education [67], precisely the groups where overweight and obesity are more common [43,59-61]. It is also common that women do not recognise themselves as being overweight or obese [68], and it seems reasonable to interpret that this may also contribute to an underestimation of associated risks. Theories on health behaviour change suggest awareness of negative outcomes to be a crucial factor in individuals’ decisions to adapt healthier behaviours [69].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the known risks of obesity on pregnancy, women who do seek preconception care are often not advised appropriately of the consequences of pre-conception obesity. One study found that only 23% of overweight women and 36% of obese women who visited a doctor prior to conceiving were advised to lose weight (35). Of women who were advised to lose weight prior to conception, this advice was most likely to come from their doctor as opposed to their mother, partner or a friend (35), therefore medical providers must take advantage of this opportunity for education and intervention.…”
Section: Discussionmentioning
confidence: 99%